Fluorinated Electrolytes for 5-V Li-Ion Chemistry: Probing Voltage Stability of Electrolytes with Electrochemical Floating Test. Issue 9 (1st January 2015) - He, Meinan; Hu, Libo; Xue, Zheng; Su, Chi Cheung; Redfern, Paul; Curtiss, Larry A.; Polzin, Bryant; von Cresce, Arthur; Xu, Kang; Zhang, Zhengcheng
Abstract : A series of electrolyte formulations containing fluorinated cyclic carbonates and fluorinated linear carbonates with LiPF6 has been evaluated as electrolyte solvents for high-voltage Li-ion batteries. The anodic stability of the new electrolytes on fully charged spinel LiNi0.5 Mn1.5 O4 (LNMO) cathode was examined by electrochemical floating tests. The effects of fluorine substitution on the cyclic and linear carbonate, ratio of cyclic vs. linear carbonate, and LiPF6 concentration on the electrolyte oxidation stability were investigated. Based on this study, the floating test proved to be an effective tool for identification of stable electrolyte materials.